2010
DOI: 10.1172/jci43271
|View full text |Cite
|
Sign up to set email alerts
|

Acute depletion of activated memory B cells involves the PD-1 pathway in rapidly progressing SIV-infected macaques

Abstract: Rapid progression to AIDS is a significant problem, especially in developing countries, where the majority of HIV-infected individuals reside. As rapid disease progression is also frequently observed in SIV-infected macaques, they represent a valuable tool to investigate the pathogenesis of this condition in humans. Here, we have shown that pathogenic SIV infection in rhesus macaques resulted in a rapid depletion (as early as week 2) of activated memory B (CD21 -CD27 + ; mB Act ) cells that was strongly associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
140
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(165 citation statements)
references
References 52 publications
21
140
3
1
Order By: Relevance
“…Later studies extended these observations to HIV/SIV-specific T cells in vitro (3)(4)(5)(6)(7). More recently, we (8,9) and others (10) have demonstrated that in vivo PD-1 blockade during chronic SIV infection restores the function of SIV-specific cellular and humoral immune responses and improves viral control. PD-1 and its ligands are expressed on many different immune cells, and thus in vivo blockade of PD-1 signaling could influence many immunoregulatory pathways.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Later studies extended these observations to HIV/SIV-specific T cells in vitro (3)(4)(5)(6)(7). More recently, we (8,9) and others (10) have demonstrated that in vivo PD-1 blockade during chronic SIV infection restores the function of SIV-specific cellular and humoral immune responses and improves viral control. PD-1 and its ligands are expressed on many different immune cells, and thus in vivo blockade of PD-1 signaling could influence many immunoregulatory pathways.…”
Section: Introductionmentioning
confidence: 81%
“…The titer of anti-Campylobacter IgG was detected as described previously for SIV-specific IgG (9), except that Campylobacter protein (2 μg/well) was used as coating antigen. T cell cytokine profiles were determined following stimulation with Campylobacter (5 μg) or Salmonella (0.5 μg) lysates as described previously (8).…”
Section: Methodsmentioning
confidence: 99%
“…PD-1 is upregulated on several lymphocytic subsets after activation. [35][36][37] Interestingly, the expression of PD-1 on T cells has been attributed to T cell exhaustion, which can be overcome by blockade of the PD1-pathway. 35,[38][39][40] The presence or absence of a pre-existing immune response to tumor-associated antigens partially represented by tumor-infiltrating memory T cells and/or PD-1 C T cells could be a very important predictive factor for immune checkpoint inhibition.…”
Section: Cd25mentioning
confidence: 99%
“…A rapid cytokine storm in acute HIV infection might also contribute to the lack of an appropriate maturing antibody response (Stacey et al 2009). Using the SIV model, it has been reported during acute infection, that there is not only a major depletion of CD4+ T cells but also a major depletion of B cells (Titanji et al 2010). In a study comparing the early immune response to two different SIV strains, with different pathological outcomes, it was shown that: early systemic immune activation, T cell proliferation, and a more prominent and broader array of cytokine/chemokine responses facilitate SIV replication, and may play a key role in persistence of infection, and the progression to AIDS (Xu et al 2011).…”
Section: Immunological Findings Of the Early Stages Of Infectionmentioning
confidence: 99%